The Effectiveness of Counseling and Assistance of Coffee Farmers in Utilizing Coffee Waste and Livestock Management - Muslim Alkautsar; Tinneke Hermina; Acep Abdul Basit (Entrepreneurship Faculty, Universitas Garut, 2023)
This study aims to determine the effectiveness of counseling and mentoring carried out for the Bina Bakti farmer group in Tanjungkarya Village. This counseling and assistance is carried out to increase the desire, knowledge and skills of farmers in utilizing coffee waste and livestock manure to become organic fertilizer. In this study a descriptive qualitative method was used to provide an overview and summarize the various circumstances or situations that occur with coffee farmers in utilizing coffee waste and livestock manure. The picture obtained shows that there are habits that are still adopted by farmers in the use of chemical fertilizers, so that coffee waste and livestock manure have not been fully utilized. The desire of farmers to process coffee waste and animal manure increased after being given counseling, because there was an increase in farmer iterations about organic fertilizers. Likewise, farmers who have used coffee waste and livestock manure to produce organic fertilizer have shown an increase in skills in production management and financial management after mentoring.